2016
DOI: 10.1155/2016/1450843
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Nicotinamide Phosphoribosyltransferase Sensitizes Glioblastoma Cells to Temozolomide via Activating ROS/JNK Signaling Pathway

Abstract: Overcoming temozolomide (TMZ) resistance is a great challenge in glioblastoma (GBM) treatment. Nicotinamide phosphoribosyltransferase (NAMPT) is a rate-limiting enzyme in the biosynthesis of nicotinamide adenine dinucleotide and has a crucial role in cancer cell metabolism. In this study, we investigated whether FK866 and CHS828, two specific NAMPT inhibitors, could sensitize GBM cells to TMZ. Low doses of FK866 and CHS828 (5 nM and 10 nM, resp.) alone did not significantly decrease cell viability in U251-MG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 65 publications
3
41
1
Order By: Relevance
“…Although numerous studies indicated that visfatin can trigger the progression of cancers including NSCLC, 10 Targeted inhibition of visfatin can sensitize glioblastoma cells to temozolomide treatment. 12 Laboratory studies also indicated that visfatin can trigger the in vitro migration and invasion of NSCLC cancers via up-regulation of MMP-2 and MMP-9. 7 Considering that migration and invasion also contribute to drug resistance, 18 our present study, together with the published data, confirmed that visfatin might be a therapy target for NSCLC to suppress its progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although numerous studies indicated that visfatin can trigger the progression of cancers including NSCLC, 10 Targeted inhibition of visfatin can sensitize glioblastoma cells to temozolomide treatment. 12 Laboratory studies also indicated that visfatin can trigger the in vitro migration and invasion of NSCLC cancers via up-regulation of MMP-2 and MMP-9. 7 Considering that migration and invasion also contribute to drug resistance, 18 our present study, together with the published data, confirmed that visfatin might be a therapy target for NSCLC to suppress its progression.…”
Section: Discussionmentioning
confidence: 99%
“…were cultured in bronchial epithelial cell basal medium (BEBM, LONZA, Wokingham, UK) supplemented with 0.1% (v/v) human recombinant epidermal growth factor and 0.1% (v/v) insulin. Cells at passage [10][11][12][13][14][15][16][17][18][19][20] were used in this study. The Dox-resistant A549/Dox and H1793/ Dox cells were selected from A549 and H1793 cells, respectively, over 6 months by selecting cells stepwise increasing concentrations of Dox (0.01-1 μmol/L).…”
Section: Beas-2b Cells Derived From Normal Bronchial Epithelial Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…JNK is upregulated in a number of tumours including GB and it has been related to glioma malignancy [29][30][31][32]. Moreover, JNK is a target for specific drugs in combination with temozolomide treatments as it was proven to play a central role in GB progression [20,[33][34][35]. However, little is known about the molecular mechanisms underlying JNK activation in glioma cells and the functional consequences for GB progression.…”
Section: Jnk Activation In Gliomamentioning
confidence: 99%
“…Glioblastoma multiforme (GB) is the most frequent and aggressive primary malignant brain tumour with a 3 per 100.000 incidence per year (Gallego, 2015). GB patients´ median survival is 12-15 months, with less than 5% of survival after 5 years (Gallego, 2015;Louis et al, 2016;McGuire, 2016;Rogers et al, 2018). The causes of GB are under debate (McGuire, 2016), 5% of the patients develop GB after a low grade astrocytoma (Alifieris and Trafalis, 2015) and the most frequent mutations include gain of function of the epidermal growth factor receptor (EGFR) (97%) and the phosphatidylinositol-3 kinase (PI3K)/phosphatase and tensin homologue (PTEN) pathways (88%) (Hayden, 2010).…”
Section: Introductionmentioning
confidence: 99%